An Improved Electronic Line Shafting Control for Multimotor Drive System Based on Sliding Mode Observer. (30th April 2019) - Geng, Qiang; Liu, Wei; Wang, Huimin; Zhou, Zhanqing; Zhang, Guozheng
Abstract : As the computation delays between the reference torques and the load torques, the speed and position synchronous errors of the multimotor drive system employed traditional electronic line shafting (ELS) control would become significant during the process of large load disturbances. Therefore, an improved ELS control strategy is proposed in this paper. In this strategy, the load torques observed by the sliding model observers are fed back to the virtual motor directly, so as to shorten the adjusting time and improve the antidisturbance performance of entire control system. Meanwhile, to reduce the chattering of the sliding mode observer, a novel exponential reaching law is designed in this paper. The experimental results show that the improved ELS control strategy could reduce the speed and position synchronous errors effectively.